Brain volumetric and microstructural correlates of executive and motor performance in aged rhesus monkeys - Sridharan, Aadhavi; Willette, Auriel A.; Bendlin, Barbara B.; Alexander, Andrew L.; Coe, Christopher L.; Voytko, Mary L.; Colman, Ricki J.; Kemnitz, Joseph W.; Weindruch, Richard H.; Johnson, Sterling C. (Frontiers in Aging Neuroscience, 2012)
The aged rhesus macaque exhibits brain atrophy and behavioral deficits similar to normal aging in humans. Here we studied the association between cognitive and motor performance and anatomic and microstructural brain integrity measured with 3T magnetic resonance imaging in aged monkeys. About half of these animals were maintained on moderate calorie restriction, the only intervention shown to delay the aging process in lower animals. T1-weighted anatomic and diffusion tensor images were used to obtain gray matter volume, and fractional anisotropy and mean diffusivity, respectively. We tested the extent to which brain health indexed by gray matter volume, fractional anisotropy, and mean diffusivity were related to executive and motor function, and determined the effect of the dietary intervention on this relationship. We hypothesized that fewer errors on the executive function test and faster motor times would be correlated with higher volume, higher fractional anisotropy, and lower mean diffusivity in frontal areas that mediate executive function, and in motor, premotor, subcortical, and cerebellar areas underlying goal-directed motor behaviors. Higher error percentage on a cognitive conceptual shift task was significantly associated with lower gray matter volume in frontal and parietal cortices, and lower fractional anisotropy in major association fiber bundles. Similarly, slower performance time on the motor task was significantly correlated with lower volumetric measures in cortical, subcortical, and cerebellar areas and decreased fractional anisotropy in several major association fiber bundles. Notably, performance during the acquisition phase of the hardest level of the motor task was significantly associated with anterior mesial temporal lobe volume. Finally, these brain-behavior correlations for the motor task were attenuated in calorie restricted animals compared to controls, indicating a potential protective effect of the dietary intervention.